The ideological use and abuse of Freiburg's ordoliberalism - Malte Dold; Tim Krieger (Public Choice, 2021)
In the aftermath of the Eurozone crisis, a battle of ideas emerged over whether ordoliberalism is part of the cause or the solution of economic problems in Europe. While German ordoliberals argued that their policy proposals were largely ignored before, during and after the crisis, critics saw too much ordoliberal influence, especially in form of austerity policies. We argue that neither view is entirely correct. Instead, we observe that the battle of ideas is largely independent of the countries' actual responses to the Eurozone crisis: pragmatic self-interest on behalf of governments rather than their ideological convictions played a crucial role in political reactions. We explain this dynamic game-theoretically and highlight a number of reasons for the decoupling of the political-pragmatic debate from the ideological-academic discourse. In addition, we argue that ordoliberals themselves contributed to the ideological misuse of their own program: the ordoliberal Freiburg School ceased to be an active research program and instead grew to resemble a tradition which all too often disregarded the international academic discourse, in particular in macroeconomics. As a result, ordoliberal thinking was abused by its proponents and critics alike to emphasize their preconceived Weltanschauung (worldview). We end our paper with some thoughts on how a contemporary ordoliberalism can be constructively used to react to some of the challenges of the ongoing Eurozone crisis.
Keywords: B29; D43; E61; G18; P16; 330; Freiburg school; Ordoliberalism; Eurozone crisis; Austerity; Ideology